Relative climatic, edaphic and management controls of plant functional trait signatures - Pakeman, Robin J; Lepš, Jan; Kleyer, Michael; Lavorel, Sandra; Garnier, Eric (Journal of vegetation science, 2009)
Objective: To identify the relative roles of climatic, edaphic and management factors in controlling the weighted mean traits of vegetation. Location: Eleven sites in Europe and one in Israel undergoing transitions in land use. Material and Methods: Standardised methods were used to collect information on species traits and attributes from plots covering a range of land uses at each site. This was combined with abundance data to create a plot x trait matrix. Variance partitioning was used to identify the relative roles of climate, soil and management on the weighted and unweighted mean traits of the vegetation in the full data set, and the data set divided into vegetative traits (including life-form, clonality, defence and a range of leaf traits) and traits linked to regeneration via seeds (including seed mass, dispersal and pollination mechanism). Results: Variance partitioning of the full data set showed that climate (18.7%), explained more variance in the weighted mean traits of the vegetation than climate and soil together (9.2), soil (6.9) and management (6.1). There was a similar distribution of variance explained for both vegetative and regeneration via seed traits, although more variance was explained for the latter. This restricted set of climatic, edaphic and management variables could explain 45-50% of the variance in the weighted mean traits of the vegetation between plots. There were only small differences between analyses of the weighted and unweighted data. Conclusions: Despite large variations in climate and soils between sites, there was still a separate and recognisable impact of management on the mean weighted traits of the vegetation. There was also a degree of shared variation between the three groups of factors, indicating that the response of plant traits to one group of factors may not be predictable because they may be modulated by their response to other groups.